A Study on Model Aircraft F1A Glider Glide Performance According to Airfoil - Son, Sung-Hwan; Jeong, Chang-Hwa; Choi, Jong-In (International Journal of Engineering and Technology, 2019)
The objective of this study was to investigate the effect of airfoil difference of F1A glider on gliding flight sink rate of model aircraft for improving competition score of F1A glider and providing basic data necessary for the development of model aircraft in Korea. Altitude Reached, set time, and sink rate were measured for a model aircraft of conventional airfoil with a large under camber and low airfoil (LDA) concept aircraft. Model aircraft of airfoil with a large under camber and model aircraft of airfoil with an LDA (low-drag airfoil) concept were constructed. They flew twice each at Osom airfield in Hwasung city, Gyeonggi province, Korea under zero wind condition. After comparing the lift-to-drag ratio of lift coefficient and drag coefficient for the angle of attack, an altimeter was installed in each model aircraft. After each flight, data of each model were analyzed and sink rate with altitude was compared. All data were analyzed using SPSS version 18.0 for Windows. Mean (M) and standard deviation (SD) were calculated. Independent sample t-test was performed to determine inter-group difference. Statistical significance level was set at p < 0.05. Results of this study were as follows. First, the optimized lift-to-drag ratio according to angle of attack was obtained through airfoil data analysis. Second, flight altitude and sink rate were determined. Third, through data analyses, a more scientific approach was made possible for competition operation.Â Â